The Evaluation Of Instructional Multimedia Product For English Learning - Farani, Rizki (English Education Department, Universitas Islam Indonesia, 2013)
Evaluating the tools that we use to share materials is important to improve the quality of learning. There are some media that we can evaluate, for instance: power point presentation, CD product, online learning, pictures, audio, etc. These media are evaluated from some perspectives, for example: the hardware/software, display of content and effectiveness in learning. In this paper, media evaluation will discuss the evaluation process of instructional multimedia product about reading comprehension in English proficiency course for college students. The product will be evaluated from the content (material, assessment test, language use, etc) and technical problems (font size of the display, color of pictures, etc). The product is developed by author by using software macromedia flash 8 (Gay, 2001:1). In previous research, this product had been validated by media and content expert and had been used to teach reading comprehension in English proficiency class. The result of the research, conducted in 2012, showed that the usage of product in learning English was good to improve students' achievement in learning. Now, author wants to evaluate the product to improve the content and revise some technical issues based on students input that is gathered by using simple questioners, designed by author and validated by media expert. It is expected that this paper can describe specifically about how to evaluate learning media in English course.Keywords: Evaluation, Instructional media, English learning